DAYA TERIMA DAN KANDUNGAN ZAT BESI KERUPUK IKAN DENGAN PENAMBAHAN TEPUNG DAUN KELOR - Sukmawati Sukmawati; Manjilala Manjilala; Chaerunnimah Chaerunnimah; Elsi Asnuraini (Media Gizi Pangan, 2023)
Background, Anemia is a condition where a person does not have sufficient iron in their body.. The 2018 Riskesdas survey recorded that the prevalence of anemia in teenagers in Indonesia was 32%. Chips is a popular dry food product that has been well-known by the Indonesian people for a long time due to its affordable price and easy availability, both in small stalls and supermarkets. Chips with the addition of fish and moringa leaf flour is expected to enrich the iron and other micro-nutrient content.Research method used in this study was pre-experimental. Three types of products were made with the addition of moringa leaf powder at concentrations of F1 (5%), F2 (10%), and F3 (15%). The acceptability was evaluated using organoleptic tests with 25 panelists. Statistical analysis was conducted using Kruskall Wallis test, and if there were differences, the Mann Whitney test was conducted. The iron content was analyzed using UV-Vis spectrophotometry.Results showed that the most acceptable fish crackers with the addition of moringa leaf powder based on color, aroma, texture, and taste were those with 5% moringa leaf powder (F1). The best formula from all aspects tested was the F1 concentration with a total score of 428, and the laboratory analysis result was 3.637 mg/100 gr.In conclusion, there were differences in the acceptability of fish crackers with the addition of moringa leaf powder in terms of color (p=0.00), aroma (p=0.00), texture (p=0.00), and taste (p=0.00). The best formula from all aspects tested was the F1 concentration, and the laboratory analysis result was 3.637 mg/100 gr.